(untitled) (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2022)
Chronic diabetic wounds are encountered as a major health problem and produced the complications of trauma. It causes long-term agony to the patients and as recurrences and post-operative complications. Consequently ‘Karam (Kshara)’- Traditional wound healing takes good hope in diabetic wound healing. This study was formulated to perceive wound healing sequels of “Manjal karasealai” (yellow corrosive gauze) on diabetic wound management. A diabetic female patient aged 65 years with having a chronic wound on the right foot was selected for this study. This lesion started six months ago and surgical wound management was done. Subsequently, the patient experienced mild symptomatic relief but it relapses repeatedly. The patient resorted to Siddha Ayurveda treatment. At first, the wound was cleaned with Tripala decoction and the fistula was identified. ‘Kshara’ technique was applied to treat this fistula as “Manjal karasealai” and inserted into the fistula by using the probe. Internal medication was given to maintain random blood sugar level below 200mg/dl. Manjal Karasealai was inserted in every other day. Size of the wound was measured for healing along with photographic images. In the end, the wound showed features of complete healing. This case study disclosed an effective wound debridement action of Manjal karasealai on a chronic diabetic wound.